Drought reduces water uptake in beech from the drying topsoil, but no compensatory uptake occurs from deeper soil layers. Issue 1 (15th October 2021) - Gessler, Arthur; Bächli, Lukas; Rouholahnejad Freund, Elham; Treydte, Kerstin; Schaub, Marcus; Haeni, Matthias; Weiler, Markus; Seeger, Stefan; Marshall, John; Hug, Christian; Zweifel, Roman; Hagedorn, Frank; et al.
Summary: The intensity and frequency of droughts events are projected to increase in future with expected adverse effects for forests. Thus, information on the dynamics of tree water uptake from different soil layers during and after drought is crucial. We applied an in situ water isotopologue monitoring system to determine the oxygen isotope composition in soil and xylem water of European beech with a 2‐h resolution together with measurements of soil water content, transpiration and tree water deficit. Using a Bayesian isotope mixing model, we inferred the relative and absolute contribution of water from four different soil layers to tree water use. Beech took up more than 50% of its water from the uppermost 5 cm soil layer at the beginning of the 2018 drought, but then reduced absolute water uptake from the drying topsoil by 84%. The trees were not able to quantitatively compensate for restricted topsoil water availability by additional uptake from deeper soil layers, which is related to the fine root depth distribution. Absolute water uptake from the topsoil was restored to pre‐drought levels within 3 wk after rewetting. These uptake patterns help to explain both the drought sensitivity of beech and its high recovery potential after drought release.